2017
DOI: 10.1039/c7tc02488f
|View full text |Cite
|
Sign up to set email alerts
|

Electrons on the surface of 2D materials: from layered electrides to 2D electrenes

Abstract: We review layered and ultrathin electrides with exciting properties like high electrical mobility, high carrier concentrations, and low work functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
57
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 107 publications
1
57
1
Order By: Relevance
“…Usually, researchers arbitrarily alter the elemental combinations of typical electrides but retain their crystal symmetry to extend for the new electrides, e.g., ABtype, A 2 B-type, and A 3 B-type (A = alkaline or rare earth elements, B = IV, V, VI, and VII elements) electrides. [24][25][26][27] Besides, many electrides (e.g., Li, 28 Na, 29 Mg, 30 C 31 , Na 2 He, 32 and Sr 5 P 3 33 ) have been found to reveal a generalized structure under pressure. 34 Depending on the dimensionality of the anionic electrons localizations, electrides can be classified into 0D, 1D, and 2D systems, 13,20,35,36 where the anionic electrons are either isolated or bonded with each other in the cage-like, channel-like, or layer-like voids.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, researchers arbitrarily alter the elemental combinations of typical electrides but retain their crystal symmetry to extend for the new electrides, e.g., ABtype, A 2 B-type, and A 3 B-type (A = alkaline or rare earth elements, B = IV, V, VI, and VII elements) electrides. [24][25][26][27] Besides, many electrides (e.g., Li, 28 Na, 29 Mg, 30 C 31 , Na 2 He, 32 and Sr 5 P 3 33 ) have been found to reveal a generalized structure under pressure. 34 Depending on the dimensionality of the anionic electrons localizations, electrides can be classified into 0D, 1D, and 2D systems, 13,20,35,36 where the anionic electrons are either isolated or bonded with each other in the cage-like, channel-like, or layer-like voids.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it was shown that Ca 2 N can be exfoliated into two-dimensional (2D) nanosheets by liquid exfoliation, while preserving anionic electrons on its surface [16,17]. Nowadays, 2D electrides, or electrenes, is a special topic of research fusing the concepts of electride chemistry and 2D materials [18].In this regards, 2D materials are of extreme interest featuring various exceptional properties and applications [19,20]. Of particular importance is intrinsic magnetism in atomically thin systems, where over the years various prototype examples have been reported to exhibit magnetic properties [21][22][23][24][25].…”
mentioning
confidence: 99%
“…Two-dimensional (2D) layered materials have displayed a new stage ever since graphene was successfully fabricated in 2004 [ 1 ]. Recently, more and more 2D materials have been synthesized and investigated [ 2 ]. These include layered transition metal dichalcogenides (TMDs) (A = Mo, W, and Re and B = S and Se) and layered group III-VI semiconductors such as GaS and GaSe.…”
Section: Introductionmentioning
confidence: 99%